Investigation of the properties of Al7075-HTC composites produced by powder metallurgy. (July 2021) - Arsun, Ozan; Akgul, Yasin; Simsir, Hamza
Even though aluminium matrix composites have been used in many different application areas, the improvement of its mechanical, tribological, and corrosion properties is crucial for enlargement of its application areas. To achieve this, many ceramic-based and carbon-based additives have been used. However, eco-friendly and low production cost hydrothermal carbons (HTCs) have not been used, yet. In this study, three different amounts of HTCs (0.25, 0.50, and 1.00 wt.%) produced from cellulose were used as a reinforcement material in Al 7075 by powder metallurgy for the first time. According to the mechanical, tribological, and corrosion test results, all of the mentioned properties of Al 7075 alloy were improved by reinforcing with HTCs. As a consequence of this study, HTCs can be used as appropriate reinforcement materials for the aluminium matrix composites.